Solvent and temperature effect in the polymorphism study of 2,6-dihydroxybenzoic acid crystal - Nur `Afifah, Mohd Mansor (2012)
This research is about the solvent and temperature effect in the polymorphism study of 2,6-Dihydroxybenzoic Acid (2,6DHB) Crystal. Polymorphism is the ability of substance to crystallize into different crystal structures. Polymorphism is important, as difference in physical properties of polymorphs can impact on issues such as solubility, bioavailability,formulation, patent protection, regulatory compliance and downstream particle handling such as filtration, drying, milling and compaction. The physical properties of polymorphs can be affected by variation of solvent and temperature. Currently, the solvent selection for crystallization is often trial and error procedure (Gu et al., 2004) and polymorphs of 2,6-DHB from some solvent is still unknown. This study is aimed to provide guideline for rational choices of solvent with different properties for polymorph screening and as extension to Adam (2011) research. The selection of solvent in this study were based on the polarity of 2,6-DHB solute and solvents molecule. Solvent chosen were Benzene Formic Acid and Diethylamine. Meanwhile, the temperature that is going to be used are 20, 35 and 50 oC. The methodology for this study is gravimetric methods for the crystallization and for analysis methods, Van’t Hoff equation, XRD, DSC, TGA and optical microscope are going to be used. But due to time limitations only optical microscope analysis method is used. Different type of solvent at specific temperatures have a significant effect in polymorphism of 2,6-DHB crystal and its physical properties. Based on the study, the rank of 2,6-DHB solubility in different solvents are Diethylamine>Formic Acid>Ideal>Benzene. Low solutesolvent interactions and poor solubility was observed in Benzene. The polymorphic characterization analysis has concluded that a Form 1 (plate-like) crystal was observed in Formic Acid and Diethylamine and the crystals are transforming to Form 2(needle-like) based on observation. Form 2(needle-like) was observed in Benzene due to prolonged time to achieve supersaturation and limitations of analysis.